A Dynamic Chemical Network for Cystinuria Diagnosis. (20th April 2018) - Lafuente, Maria; Solà, Jordi; Alfonso, Ignacio
Abstract: The study of molecular networks represents a conceptual revolution in chemistry. Building on previous knowledge and after understanding the rules of non‐covalent interactions, the design of stimulus‐responsive chemical systems is possible. Herein we report a new strategy, based on the reorganization of a dynamic chemical network that generates new fluorescent associations in the presence of cysteine or cystine. The binding and sensing units are encoded in the components that dynamically assemble and disassemble responding to external stimuli as a successful tool to detect both cysteine and cystine in aqueous media. Moreover, the dynamic sensing system works in human urine, as a prospective application for cystinuria diagnosis. Abstract : Cystinsystem : Ein dynamisches kovalentes chemisches System lagert sich in Gegenwart von Cystein und Cystin um und erzeugt dabei ein Fluoreszenzsignal. Das chemische System kann zum Nachweis von pathologischen Mengen des Biothiols im Urin genutzt werden.